2005
DOI: 10.1007/s10750-004-4672-y
|View full text |Cite
|
Sign up to set email alerts
|

Coral mass- and split-spawning at a coastal and an offshore Venezuelan reefs, southern Caribbean

Abstract: This study aimed to evaluate potential differences in coral spawning behavior between a fringing coastal reef and an offshore reef in the southern Caribbean. For this, scleractinian and gorgonian colonies (N = 324) of 21 species were mapped along eight transects, each 10-m long, at two study sites located in Morrocoy and Los Roques National Parks, Venezuela. Observations were made between 19:30 and 23:00 from August 23 to 30 and from September 26 to 30, 2002. Ninety one colonies belonging to six hard coral and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 14 publications
4
26
3
Order By: Relevance
“…Sexual reproduction failure in anthozoans has been associated with many sources of stress including those mentioned above (turbidity/sedimentation, eutrophication, mechanical stress, oil and chemical pollution, bleaching, UV radiation), and recently, as shown in this study, biotic diseases play an important role. While previous spawning observations have shown healthy-looking tissues in colonies with YBD-releasing bundles (Bastidas et al 2005), results of the present study provide the first quantitative evidence of infertility in polyps affected by the disease, and a significant reduction in fecundity in polyps close to the lesion. Although no significant differences were found, the trend observed indicated that YBD might have a systemic effect, affecting healthy-looking tissues far from the active lesions in infected colonies.…”
Section: Discussionsupporting
confidence: 44%
“…Sexual reproduction failure in anthozoans has been associated with many sources of stress including those mentioned above (turbidity/sedimentation, eutrophication, mechanical stress, oil and chemical pollution, bleaching, UV radiation), and recently, as shown in this study, biotic diseases play an important role. While previous spawning observations have shown healthy-looking tissues in colonies with YBD-releasing bundles (Bastidas et al 2005), results of the present study provide the first quantitative evidence of infertility in polyps affected by the disease, and a significant reduction in fecundity in polyps close to the lesion. Although no significant differences were found, the trend observed indicated that YBD might have a systemic effect, affecting healthy-looking tissues far from the active lesions in infected colonies.…”
Section: Discussionsupporting
confidence: 44%
“…Based on previous fecundity and fertilization rate studies (e.g. Van Veghel & Kahmann 1994, Hughes et al 2000, Bastidas et al 2005), the source reefs should produce at least 1.5 × 10 6 times more viable planulae than the number of particles released in the model. The particle concentrations were therefore also multiplied by a factor of 1.5 × 10 6 .…”
Section: Data Extractionmentioning
confidence: 99%
“…Between these extremes are a variety of complex patterns of spawning and planulation, ranging from (3) coincident multispecific spawning in a few species and (4) temporal isolation of reproduction in other species in the Caribbean and western Atlantic (e.g. Szmant 1986, Gittings et al 1992, Van Veghel 1993, Hagman et al 1998, Bastidas et al 2005, to (5) extensive multispecific spawning and (6) other reproductive patterns in some Indo-Pacific tropical and subtropical reef regions, which vary in scale and the extent of breeding seasons (e.g. Hayashibara et al 1993, Richmond 1997, Baird et al 2001, Wilson & Harrison 2003, Guest et al 2005a,b, Penland et al 2004, Caroll et al 2006, Harrison 2008, Rosser & Gilmour 2008.…”
Section: Introductionmentioning
confidence: 99%